2009
DOI: 10.1371/journal.pone.0008084
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Discovery of Vaccine Adjuvants: Coupling In Silico Screening and In Vitro Analysis of Antagonist Binding to Human and Mouse CCR4 Receptors

Abstract: BackgroundAdjuvants enhance or modify an immune response that is made to an antigen. An antagonist of the chemokine CCR4 receptor can display adjuvant-like properties by diminishing the ability of CD4+CD25+ regulatory T cells (Tregs) to down-regulate immune responses.MethodologyHere, we have used protein modelling to create a plausible chemokine receptor model with the aim of using virtual screening to identify potential small molecule chemokine antagonists. A combination of homology modelling and molecular do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 60 publications
(72 reference statements)
4
54
0
1
Order By: Relevance
“…This CCR4 antagonist was previously shown to block in vitro the migration of human Tregs mediated by CCL22 or CCL17 and to increase humoral and cellular responses against various bacterial and viral Ags. 14,15 This study confirms and extends these results by showing the ability of this CCR4 antagonist to break tolerance in models, where Tregs play a main role in the control of anti-self CD8 ϩ T cells. Compared with conventional approaches to block Tregs (anti-CD25 mAb, cyclophosphamide), we show that this CCR4 antagonist appears to be a competitive strategy.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…This CCR4 antagonist was previously shown to block in vitro the migration of human Tregs mediated by CCL22 or CCL17 and to increase humoral and cellular responses against various bacterial and viral Ags. 14,15 This study confirms and extends these results by showing the ability of this CCR4 antagonist to break tolerance in models, where Tregs play a main role in the control of anti-self CD8 ϩ T cells. Compared with conventional approaches to block Tregs (anti-CD25 mAb, cyclophosphamide), we show that this CCR4 antagonist appears to be a competitive strategy.…”
supporting
confidence: 79%
“…In vitro experiments in humans showed that these CCR4 antagonists inhibit the recruitment of Tregs mediated by CCL22 and CCL17 and, when administered in combination with vaccines, increased humoral responses against foreign Ags. 14, 15 The present study was designed to address whether a CCR4 antagonist (a small chemical molecule with a molecular weight of 565.93; contain six 5-or 6-membered aromatic rings; and 3 nitrogen atoms) previously described 14 was efficient to elicit CD8 ϩ T cells directed against various self Ags. Tregs are known to exert a stringent peripheral control on these anti-self CD8 ϩ T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we would like to speculate that our analysis would render the designing and development of peptidomimics that specifically inhibit interaction between Rv1917c and pattern recognition receptors as well as host signaling proteins of DCs or macrophages. Because expansion of regulatory T cells and Th2 cells is a hallmark of chronic tuberculosis infection, the molecular adjuvants such as CCR4 antagonists that block these two suppressive populations might benefit tuberculosis vaccination strategies (79,80). These insights, in our opinion, will broaden the understanding of the tuberculosis disease pathogenesis and might pave a way for their inclusion in drug development efforts against tuberculosis.…”
Section: Discussionmentioning
confidence: 95%
“…To understand the role of chemokine-mediated function in the immune response, attention has focused on receptor biology more so than that of the individual chemokines [2][3][4][5][6][7] . One approach to study CCR4 biology has been to employ knock-out (KO) mice which, while informative, fail to adequately address the different functional consequences of CCL17 and CCL22 engagement with CCR4.…”
Section: Introductionmentioning
confidence: 99%